Analysis of protein profiling studies of β‐thalassemia/Hb E disease. Issue 11 (9th September 2016) - Lithanatudom, Pathrapol; Smith, Duncan R.
Abstract : A number of studies have used global protein profiling technologies on a range of patient samples to detect proteins that are differentially expressed in β‐thalassemia/Hb E as an aid for understanding the physiopathology of this disease. Seven studies have identified a total of 111 unique, differentially expressed proteins. Seven proteins (prothrombin, alpha‐1‐antichymotrypsin, fibrinogen beta chain, hemoglobin beta, selenium‐binding protein, microtubule‐actin cross‐linking factor and adenomatous polyposis coli protein 2) have been identified in two independent studies, whereas two proteins (carbonic anhydrase 1 and peroxiredoxin‐2) have been identified in three independent studies. Both of these latter two proteins were consistently upregulated in the studies that identified them. Ontological analysis of all differentially regulated proteins identified "response to inorganic substances" as the most significant functional annotation cluster, which is consistent with iron overload being a major pathological consequence of this disease. Despite the range of samples investigated and the relatively small number of studies undertaken, a coherent picture of the mediators of the pathological consequences of β‐thalassemia/Hb E disease is starting to emerge.